Developing the impact of vision impairment–very low vision (IVI-VLV) questionnaire as part of the LoVADA protocol - Finger, Robert; Tellis, B.; Crewe, Julie; Keeffe, J.; Ayton, L.; Guymer, R. (The Association for Research in Vision and Ophthalmology, Inc., 2014)
PURPOSE: To design and evaluate an instrument appropriate for assessing vision-related quality of life (VRQoL) in persons with severe vision loss. METHODS: A total of 603 legally blind persons (better eye visual acuity of <20/200) were interviewed using an item pool based on the original Impact of Vision Impairment (IVI) questionnaire, augmented by items appropriate for persons with severe vision loss. Refinement and item reduction was done in three steps using factor and Rasch analysis to assess psychometric properties, exploring key indices, such as response category functioning (floor and ceiling effects), instrument unidimensionality, discriminant ability, and targeting of item difficulty to patient ability. RESULTS: A final pool of 28 items was selected that grouped into two subscales of the IVI-VLV: activities of daily living, mobility, and safety (ADLMS; 16 items) and emotional well-being (EWB; 12 items). Both subscales are unidimensional, able to differentiate reliably between at least three different levels of VRQoL, and item difficulty was adequate for the assessed sample. Using generalized linear models and controlling for age, we found that only poor general health (P ¼ 0.005 and P ¼ 0.007) and concurrent depression and anxiety (P ¼ 0.019 and P < 0.001) were associated with a lower ADLMS and EWB subscale score, respectively. CONCLUSIONS: The IVI-VLV is a valid and reliable VRQoL measure in persons with severe vision loss, and its measurement is almost unaffected by participants’ self-perceived general or mental health. The IVI-VLV can be used as an outcome measure in trials attempting sight restoration.